An approach to multi‐attribute assessment of indoor environment before and after refurbishment of dwellings - Zavadskas, Edmundas Kazimieras; Kaklauskas, Arturas; Kalibatas, Darius (Journal of Environmental Engineering and Landscape Management, 2009)
The paper analyses the correspondence between the present state of indoor environment and needs of habitants and the Lithuanian Hygienic Norm. To investigate the correspondence the authors (a) distinguish measures (attributes) of evaluating dwelling houses and their importance, (b) choose a method of processing the values of attributes, (c) choose a method of evaluating the efficiency of refurbishment and/or renovation of a building and (d) investigate dwelling houses in Naujoji Vilnia and evaluate the efficiency of refurbishment and/or renovation. As a result of the analysis the authors propose an approach to multi‐attribute assessment of dwelling houses before and after refurbishment and/or renovation and evaluation of its efficiency. The experiment results, obtained by measuring five dwellings in Naujoji Vilnia, show that the renovation process was the most efficient for the second dwelling.Daugiatikslio gyvenamųjų namų vidinės aplinkos vertinimo prieš ir po renovacijos būdasSantrauka. Nagrinėjama, kaip gyvenamųjų namų vidinė aplinka atitinka gyventojų poreikius ir Lietuvos higienos normas. Išvados gali būti daromos: a) nustačius rodiklius, pagal kuriuos galima vertinti gyvenamuosius namus, ir jų reikšmingumą, b) pasirinkus rodiklių apdorojimo metodą ir c) pasirinkus metodą renovacijos efektyvumui nustatyti. Pateiktas daugiatikslis vidinės aplinkos vertinimo prieš ir po renovacijos bei renovacijos efektyvumo nustatymo būdas. Šis būdas pritaikytas penkiems gyvenamiesiems namams Naujojoje Vilnioje (Vilnius) įvertinti.Reikšminiai žodžiai: vidinė aplinka, daugiatikslis vertinimas, efektyvumas, gyvenamasis namas, Lietuvos higienos normos, daugiatikslio naudingumo funkcija.Комплексная оценка внутренней среды жилых домов до и после реновацииРезюме. Жилые дома Литвы не всегда соответствуют литовским нормам гигиены (HN 42:2004) и потребностям жителей. Поэтому они нуждаются в реконструкции. Несоответствие литовским нормам гигиены (HN 42:2004) может быть установлено не только по жалобам жителей, но и по результатам измерения внутреннего климата жилья. При этом важно (а) установить критерии оценки климата жилья и их приоритеты, (б) подобрать метод для обработки данных по установленным критериям оценки климата и их приоритетам, (в) подобрать метод для установления необходимой реконструкции и ее эффективности. Авторы предлагают метод многокритериальной оценки жилых домов до и после реновации и установления эффективности реконструкции жилых домов. Предложенный метод был применен для многокритериальной оценки жилых домов в Новой Вильне.Ключевые слова: внутренний климат, многокритериальная оценка, эффективность, жилой дом, литовские нормы гигиены, многокритериальная функция эффективности. First Published Online: 14 Oct 2010